Modeling energy governance index for the adequacy of policy, legal, and institutional response measures for climate compatible development - Iqbal, Kanwar Muhammad Javed; Waheed, Farah; Azhar, Urooj; Akhtar, Nadia; Khan, Muhammad Irfan (Frontiers in Environmental Science, 2022)
Climate compatible and sustainable expansion of energy resources is a major global challenge. Developing countries, with inadequate resources and incoherent policies, legal and institutional frameworks, must strive hard to achieve targets set under Sustainable Development Goals (SDGs) while keeping track of Nationally Deter-mined Contributions (NDCs) for Greenhouse Gas (GHG) emissions abatement. Inclusive governance is quite complex due to interplay of informal and formal system, rules-based to rights-based approaches and arrange-ments in national to local scenarios vis-a-vis methodological limitations. In the context, this paper aimed at de-veloping governance index for assessing climate compatible development (CCD) by taking case of energy sector in Pakistan. A multivariate analysis model was deployed by combining MCDA method with statistical analysis of data collected from respondents through key informant interviews (340) and focus group discussion (17), against climate response and principles of good governance, nine (09) CCD criteria and 43 composite indicators at federal, provincial and district level. Findings decipher the dearth of a preemptive and comprehensive gov-ernance framework to address CCD in energy sector at all tiers of constituencies in Pakistan. There is a need for coherent and inclusive policy, legal and institutional framework. This study’s outcome authenticates the findings of United Nations SDGs Report 2020.